2012
DOI: 10.1186/1471-2164-13-275
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing spatiotemporal dynamics of apoptosis after G1 arrest by human T cell leukemia virus type 1 Tax and insights into gene expression changes using microarray-based gene expression analysis

Abstract: BackgroundHuman T cell leukemia virus type 1 (HTLV-1) Tax is a potent activator of viral and cellular gene expression that interacts with a number of cellular proteins. Many reports show that Tax is capable of regulating cell cycle progression and apoptosis both positively and negatively. However, it still remains to understand why the Tax oncoprotein induces cell cycle arrest and apoptosis, or whether Tax-induced apoptosis is dependent upon its ability to induce G1 arrest. The present study used time-lapse im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
1
4
0
1
Order By: Relevance
“…The difference in cell cycle between healthy subjects and HTLV-1 infected could be a causality of the HTLV-1 infection. Our results are in agreement with Arainga et al (2012) who also described cell cycle arrest at G 1 phase by human T-cell lymphotropic virus type-1 Tax protein in HeLa cells in vitro. Liu et al (2008) have also showed cell cycle arrest at G 1 phase triggered by Tax viral protein transfection and subsequent apoptosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The difference in cell cycle between healthy subjects and HTLV-1 infected could be a causality of the HTLV-1 infection. Our results are in agreement with Arainga et al (2012) who also described cell cycle arrest at G 1 phase by human T-cell lymphotropic virus type-1 Tax protein in HeLa cells in vitro. Liu et al (2008) have also showed cell cycle arrest at G 1 phase triggered by Tax viral protein transfection and subsequent apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…In an alternative hypothesis, HTLV-1 particles and viral proteins may be interfering in the host cell cycle regulators, delaying cell division. As described above, Tax viral protein has been associated with cell cycle abnormalities such as G 0 /G 1 delay (Liu et al, 2008;Arainga et al, 2012). On the other hand, it is possible that the virus is subverting the host biological machinery in its own benefit in order to produce proteins to supply the virus necessities.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report identified lower CD40LG expression in cells expressing PTHrP and MIP-1α, two proteins associated with ATLL progression (Shu et al, 2012). The second marker identified herein, GBP2 , was previously associated with tax protein activity in HTLV-1 (Arainga et al, 2012). Despite identifying these associations, no previous studies proposed either of these genes as biomarkers of ATLL or HAM/TSP symptomatology.…”
Section: Discussionmentioning
confidence: 69%
“…Tax activates viral and cellular gene expression. Its oncogenic potential depends on its ability to alter the expression of cellular genes involved in cell growth and proliferation and their direct interactions with the cycle regulators ( 41 , 42 ). Although antigenic, clone A8 was not an accessible mimetic and hydrophilic peptide.…”
Section: Discussionmentioning
confidence: 99%